PENTINGNYA PEMAHAMAN PASIEN TERHADAP BAHAN LENSA KONTAK LUNAK DAN JANGKA WAKTU PEMAKAIAN DI OPTIK KOTA PADANG - Febry Corina; Alvia Wesnita; Peni Okto Randi; Alwa Pascaselnofra Amril (Ensiklopedia of Journal, 2023)
This study discusses the importance of patient understanding of soft contact lens materials and the period of use in Optik Kota Padang. This study aims to reveal: (1) patients' understanding of soft contact lens materials and the duration of use, (2) the impact of soft contact lens use on lens materials and the duration of use, (3) handling of the impact of soft contact lens use on lens materials and the period of use. Data was collected through questionnaires at Optik Kota Padang. Then the data is discussed based on the theory proposed in the literature review and presents the results of respondents' answers in Optik Kota Padang in order based on the problem formulation. The research method used is quantitative descriptive method. Of the 30 respondents, 19 respondents (63.3%) had a fairly good understanding of soft contact lens materials and the correct wearing life, while 11 respondents (36.7%) did not have an understanding of soft contact lens materials and the correct wearing period. The impact of soft contact lens use and prolonged usage period in Padang City Optics can be seen that as many as 17 respondents (56.7%) know and have felt the impact of soft contact lens use and prolonged wearing period, while as many as 13 respondents (43.3%) do not know and have never felt the impact of soft contact lens use and prolonged use. The impact of soft contact lens use and wearing period can be seen that 18 respondents (60%) know how to overcome the impact of soft contact lens use and prolonged contact lens use, while 12 respondents (40%) do not know how to overcome the impact of contact lens use and prolonged contact lens use.